(untitled) (Revista de Ciências Agroveterinárias, 2007)
The straw presence on the soil surface can reduce the emergence and growth of weeds in no tillage system. The straw ability to reduce weed infestation in maize depends on the desiccation time in relation to maize sowing. The aim of this work was to evaluate the effects of winter cover crops desiccated in different times on the weed infestation and maize grain yield. The experiment was carried out in Papanduva, SC, Brazil, using a randomized blocks design. Seven cover crops were evaluated: black oat, ryegrass, rye, common vetch, oilseed radish, intercropping among black oat and common vetch and intercropping among black oat, ryegrass, rye, common vetch and oilseed radish. The cover crops were desiccated 1 and 27 days before maize sowing. Maize plants were kept in the presence and absence of weeds. Oilseed radish and common vetch produced straw with reduced potential to suppress weed development. The winter cover crops desiccation 27 days before maize sowing increased weed infestation. In weed absence, the kind of winter cover crop and its temporal desiccation did not affect maize grain yield.